Power Output Characteristics of Offshore Wind Farms – Modelling of Feed-in Fluctuations at German Offshore Wind Farm Locations - Bendfeld, Jörg; Splett, Michael (Proceedings of the DEWEK 2010)

Dynamic mechanical load tests on crystalline silicon modules. - Kupke, J.; Koch, S.; Penidon, R.; Schoppa, M; Krauter, Stefan; Grunow, Paul (Proceedings of the 25th European Photovoltaic Solar Energy Conference and Exhibition, Valencia (Spanien), September 6-10, 2010)

Konzept zur nachhaltigen Integration der Offshore-Windenergie mittels dezentraler Biogasnutzung - Bendfeld, Jörg; Tigges, Martin; Splett, Michael (Wissenschaftliche Verhandlungen 2010 der Deutschen Physikalischen Gesellschaft, Hannover, März 2010)

Draft proposal for an Offshore Metmast for Renewable Energy - Bendfeld, Jörg; Tigges, Martin; Splett, Michael (Wissenschaftliche Verhandlungen 2010 der Deutschen Physikalischen Gesellschaft, Hannover, März 2010)

Wave measurements with different principles (ast and bouy) - Bendfeld, Jörg; Tigges, Martin; Splett, Michael (Wissenschaftliche Verhandlungen 2010 der Deutschen Physikalischen Gesellschaft, Hannover, März 2010)

Energy feed characteristics of offshore wind farms – a modeled analysis of single and clustered farms - Bendfeld, Jörg; Krieger, Jens; Splett, Michael (Proceedings of the European Wind Energy Conference & Exhibition (EWEC 2010))

Reducing the offshore wind farm feed-in fluctuations by fast reacting biogas plants - Bendfeld, Jörg; Krieger, Jens; Splett, Michael (Proceedings of the European Wind Energy Conference & Exhibition (EWEC 2010))

Measurements for wave and current modeling regarding offshore-windfarms - Bendfeld, Jörg; Krieger, Jens; Splett, Michael (Proceedings of the European Wind Energy Conference & Exhibition (EWEC 2010))

Advanced,multipurpose offshore-metmast - Bendfeld, Jörg; Krieger, Jens; Splett, Michael (Proceedings of the European Wind Energy Conference & Exhibition (EWEC 2010))

Variations of pricing at energy markets caused by energyfeed of offshore wind farms - Bendfeld, Jörg; Krieger, Jens; Splett, Michael (Proceedings of the European Wind Energy Conference & Exhibition (EWEC 2010))

Optimization of the energy feed-in for renewable energies - Bendfeld, Jörg; Tigges, Martin; Splett, Michael; Wollenberg, J.; Krieger, Jens (Proceedings of the ICCI2010, 16. International Energy & Environment Fair & Conference)

Deutschland geht Offshore - Bendfeld, Jörg

Wave and Current measurements for Offshorwindfarms - Bendfeld, Jörg; Madge, S.; Splett, Michael; Krieger, jens (Proceedings of the North American Offshore Wind Conference &Exhibition, October 5.-7, 2010)

Advanced design for an Offshore Metmast - Bendfeld, Jörg; Madge, S.; Splett, Michael; Krieger, jens (Proceedings of the North American Offshore Wind Conference &Exhibition, October 5.-7, 2010)

Functional Design for an Offshore Metmast - Bendfeld, Jörg; Krieger, Jens; Splett, Michael (Proceedings of the German Wind Energy Conference (DEWEK 2010))

5 Years Offshore Metmast Amrumbank West - Bendfeld, Jörg; Splett, Michael (Proceedings of the DEWEK 2010)

Wave Measurements forOffshore Wind Power Work and Safety - Bendfeld, Jörg; Splett, Michael (Proceedings of the DEWEK 2010)

Balancing Feed-in Fluctuations of Offshore Wind Farmswith Biogas Fired Turbines - Bendfeld, Jörg; Tigges, Martin; Splett, Michael (Proceedings of the DEWEK 2010)

Supporting offshore wind energy generation through biogas power plants - Bendfeld, Jörg; Splett, Michael; Tigges, Martin; Krauter, Stefan (Proceedings of the 5th InternationalRenewable Energy Storage Conference (IRES2010))

Operation Management for Coping with Wakes within Offshore Wind Farms - Kobialka, Hans-Ulrich; Schulz, Viktor; Splett, Michael; Bendfeld, Jörg (Proceedings of the DEWEK 2010)

Flasher tolerances of powermeasurement on μ-morph tandem modules - Böttcher, A.; Prorok, A.; Ferretti, N.; Krauter, Stefan; Grunow, Paul (Proceedings of the 25th European Photovoltaic Solar Energy Conference and Exhibition, Valencia (Spanien), September 6-10,2010)

Performance comparison of a-Si, μ-Si, and c-Si as a function of air mass and turbidity. - Preiss, A.; Krauter, Stefan (Proceedings of the 25th European Photovoltaic Solar Energy Conference and Exhibition, Valencia (Spanien), September 6-10,2010)

Berufliches Lernen mit Web 2.0 - Medienkompetenz und berufliche Handlungskompetenz im Duell? - Pferdt, F. G.; Kremer, H.-Hugo (Jahrbuch Medienpädagogik 8. Medienkompetenz und Web 2.0)

Implementation von Curricula am Beispiel der Lernfeldinnovation - Buschfeld, D.; Kremer, H.-Hugo (Handbuch Berufs- und Wirtschaftspädagogik)

Bildung in Zeiten neuer Medien aus berufs- und wirtschaftspädagogischer Perspektive - Kremer, H.-Hugo (Bildung und Unterricht in Zeiten von Google und Wikipedia)

Tandem: Ausbildungsfähigkeit von Gefangenen und Gewaltprävention im Strafvollzug - Kremer, H.-Hugo; Gebbe, M.; Wirth, W. (Bewährungshilfe. Soziales - Strafrecht - Kriminalpolitik)

Individuelle Förderung - aber wie? Einblicke in das Innovationsprojekt InLab - Kremer, H.-Hugo; Frehe, Petra (Wirtschaft und Erziehung)

Kompetenzdiagnose als Basis individueller Förderung - Zum Geheimnis einer Black Box!? - Kremer, H.-Hugo; Zoyke, A. (Kompetenzermittlung für die Berufsausbildung. Verfahren, Probleme und Perspektive im nationalen, europäischen und internationalen Raum)

Transgressive Melodrama. The 'Sensational' 1860s and their After-Effects - Tönnies, Merle (Victorian Highways - Victorian Byways. New Approaches to Nineteenth-Century British Literature and Culture)

Proceedings of the 22nd ACM symposium on Parallelism in algorithms and architectures - SPAA '10 - Meyer auf der Heide, Friedhelm; Phillips, Cynthia A.

Internationale Personalwirtschaft und Internationales Arbeitsrecht

Preprocessed Global Visibility for Real-Time Rendering on Low-End Hardware - Eikel, Benjamin; Jähn, Claudius; Fischer, Matthias (Advances in Visual Computing)
We present an approach for real-time rendering of complex 3D scenes consisting of millions of polygons on limited graphics hardware. In a preprocessing step, powerful hardware is used to gain fine granular global visibility information of a scene using an adaptive sampling algorithm. Additively the visual influence of each object on the eventual rendered image is estimated. This influence is used to select the most important objects to display in our approximative culling algorithm. After the visibility data is compressed to meet the storage capabilities of small devices, we achieve an interactive walkthrough of the Power Plant scene on a standard netbook with an integrated graphics chipset.

Continuous and Discrete Concepts for Detecting Transport Barriers in the Planar Circular Restricted Three Body Problem - Dellnitz, Michael; Padberg, Kathrin; Preis, Robert; Thiere, Bianca (Nonlinear Science and Complexity)

Solving optimal control problems by using inherent dynamical properties - Flaßkamp, Kathrin; Ober-Blöbaum, Sina; Kobilarov, Marin (PAMM)

Spacecraft trajectories to the L3 point of the Sun–Earth three-body problem - Tantardini, Marco; Fantino, Elena; Ren, Yuan; Pergola, Pierpaolo; Gómez, Gerard; Masdemont, Josep J. (Celestial Mechanics and Dynamical Astronomy)

Detecting Initial Guesses for Trajectories in the (P)CRTBP - Thiere, Bianca; Ober-Blöbaum, Sina; Pergola, Pierpaolo (AIAA/AAS Astrodynamics Specialist Conference)

Das Gendiagnostikgesetz - Krimphove, Dieter (Arbeit und Arbeitsrecht (AuA))

Im Überblick: Die Beteiligungsrechte des Betriebsrats - Krimphove, Dieter (Der Betriebsrat)

Brauchen wir die Europäische Genossenschaft? - Krimphove, Dieter (EuZW)

Computergestützte traumatherapeutische Behandlungsmöglichkeiten bei Verkehrsunfallopfern von Kindern und Jugendlichen - Huck, Wilfried; Alakbarov, Alexej; Domik, Gitta; Radkowski, Rafael; Tölke, Roswitha; Mikus, Ann-Cathrin; Geisen, Silke (12. Jahrestagung der Deutschsprachigen Gesellschaft für Psychotraumatologie (DeGPT))

Edoardo Ferrante: Consensualismo e Trascrizione, Cedam Padova, 2008, pp I-XIV; 1-367 - Krimphove, Dieter (Rivista Trimesttriale di Diritto e Procedura Civile Anno LXIV Fasc.)

Preisfindung für hybride Leistungsbündel--Modellbasierte Integration von Ansätzen zur Entscheidungsunterstützung - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Müller, Oliver (Dienstleistungsmodellierung 2010)

Online-Produktkonfiguratoren – Status quo und Entwicklungsperspektiven - Becker, Jörg; Knackstedt, Ralf; Müller, Oliver; Benölken, Alexander; Schmitt, Oliver; Thillainathan, Mayooran; Schulke, André (Vertriebsinformationssysteme)

An ontology-based natural language service discovery engine--design and experimental evaluation - Becker, Jörg; Müller, Oliver; Woditsch, Manuel (European Conference on Information Systems)

Proof-Carrying Hardware: Concept and Prototype Tool Flow for Online Verification - Drzevitzky, Stephanie; Kastens, Uwe; Platzner, Marco (International Journal of Reconfigurable Computing)

Virtuelle Speicherverwaltung für Hardware Threads in Rekonfigurierbaren Systemen - Agne, Andreas

EMG-basierte Ganganalyse - Boschmann, Alexander

Evolvable Cache Controller - Breitlauch, Daniel

Soft Microprocessors with tightly coupled Application-Specific Coprocessors - Dridger, Denis

Parallelization of the UCT Algorithm on HPC-Clusters - Graf, Tobias